(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Public personnel administration, which is a significant aspect of public administration in the modern state, is rightly described by Herman Finer, a renowned British social scientist, as the sovereign factor in public administration. It is also called by such names as manpower management, personnel management, labour welfare management, and so on. The term personnel administration is known to have a wider connotation as it deals with numerous elements as classification is civil servants, recruitment, training, promotion, compensation, discipline and retirement benefits of the personnel in the government.